Ecological assessment of the heavy metals content in soils in Zhytomyr region - Стежко, О. В. (Scientific Progress & Innovations, 2012)
One of the most common soil contaminants are heavy metals. They enter in the soil as a result of anthropogenic factors, one of which is human activity. On agricultural lands in private ownership over 60 % of crop production is grown, so the analysis of heavy metals in these areas is very important. This work presents the results of researches of the heavy metals content in the arable soil layer which was selected from the private farms of the village Volitsa, Zhytomir region.